OPTIMASI PRODUKSI MICROBIAL-CELLULOSE DALAM BIOREAKTOR DRUM BERPUTAR (Rotary Drum Bioreactor) - PARLUHUTAN PARLUHUTAN; FAJAR RESTUHADI; NOVIAR HARUN (Universitas Riau, 2016)
The purpose of this study is to design an innovative bioreactors drum that potentially obtain the maximum ofmicrobial cellulose and to determine the drum rotation on contact time of Acetobacter xylinum with nutrientsand air by slowly rotation. The tools designed on 5,10, 15, 20, and 25 rpm to obtain the best optimization ofmicrobial cellulose by comparing with a static culture. The best result of descriptive analysis andexperimentation ware at a speed of 5 rpm with wet weight of 981 gr, dry weight 68,86 gr, the thickness 5,31mm, 44,42% of yield, 92,89% of water content, total of sugars before fermented was 13.66% and after fermentedfor 5 days is 6,69%, with the percentage of reduction of 6,67% sugar synthesized by Acetobacterxylinum cell.